Do Pre-1970 Precedents Still Matter? An Empirical Analysis of Legal Submissions and Court Decisions - Warchuk, Paul (McGill Law Journal / Revue de droit de McGill, 2025)
This paper examines the contemporary relevance of pre-1970 Supreme Court of Canada decisions through quantitative citation analysis, responding to Chief Justice Wagner’s 2024 assertion that these historical decisions are of minimal legal interest. The study analyses three datasets: citations in Supreme Court decisions (1985–2024), appeal factums (2009–2024), and decisions from all Canadian courts and tribunals on CanLII. The evidence contradicts the chief justice’s assertions. Pre-1970 cases appear in over half of Supreme Court decisions and one-quarter of factums filed between 2015–2024. This engagement spans 2,100 unique pre-1970 decisions. Qualitative analysis reveals that lawyers and judges invoke these precedents primarily as binding legal authority (77.6%) rather than historical background. Contrary to claims that older precedents are irrelevant in commercial matters, this area demonstrates the highest rate of pre-1970 citations. Surprisingly, French-language factums cite untranslated pre-1970 decisions more frequently than English ones, and Chief Justice Wagner himself ranks among justices most likely to cite pre-1970 cases. The paper concludes that pre-1970 decisions continue to meaningfully influence Canadian jurisprudence, particularly in certain legal domains, suggesting that official translations would serve a valuable purpose.